2021
DOI: 10.3390/ijerph18147434
|View full text |Cite
|
Sign up to set email alerts
|

The Affective Domain—A Program to Foster Social-Emotional Orientation in Novice Physical Education Teachers

Abstract: The present study aimed to assess the influence of an emotional-based program for novice physical education teachers on their perception of the affective domain in teaching, and the influence of the program on their social-emotional orientation. Thirty-two physical educators in their induction year participated. Instrumentations included reflective assignments: individual tasks, a group artwork task, short videos containing student–teacher scenarios, and summary reflections. The study covered tasks that contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Effective research can be carried out during distance learning if these six aspects can be appropriately implemented. Next research Zach and Rosenblum (2021) results that affective assessment in distance learning, students feel to experience the emotional awareness they have and a sense of empathy for others affects students' social orientation. and research Shearer et al (2021) concluded that affective assessment requires adequate instruments and adapts to distance learning strategies in order to get the results that are expected in distance learning.…”
Section: The Benefits Of Affective Assessment In Social Studies Learn...mentioning
confidence: 86%
“…Effective research can be carried out during distance learning if these six aspects can be appropriately implemented. Next research Zach and Rosenblum (2021) results that affective assessment in distance learning, students feel to experience the emotional awareness they have and a sense of empathy for others affects students' social orientation. and research Shearer et al (2021) concluded that affective assessment requires adequate instruments and adapts to distance learning strategies in order to get the results that are expected in distance learning.…”
Section: The Benefits Of Affective Assessment In Social Studies Learn...mentioning
confidence: 86%
“…In terms of learning methods, the conclusion shows that the variety of learning methods used by teachers, such as demonstrations, assignments to students, games, group discussions, and projects, provide varied learning experiences for students and can help increase student motivation and involvement in learning. Physical education is able to stimulate physical and non-physical aspects concerning work ability, thinking and skills so that the improvement of the quality of strong human resources can be achieved (Croston & Hills, 2017); (Claudia, 2022); (Zach & Rosenblum, 2021).…”
Section: Process Evaluationmentioning
confidence: 99%
“…In physical education, emotional education for students can not only mobilize students' good emotions, but also optimize teaching effect and improve teaching quality (Zach and Rosenblum, 2021). The five functions of physical education are shown in Figure 2.…”
Section: Teaching Goals Of Emotional Educationmentioning
confidence: 99%